2009
DOI: 10.1111/j.1540-6210.2009.02035.x
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Privatization Strategies 25 Years Later: Revisiting Perry and Babitsky's Comparative Performance Study of Urban Bus Transit Services

Abstract: When assessing contracting out or privatization gains in the area of local government transportation, factors such as the mode of transportation provided, population density, and type of government may be the most infl uential factors in determining the effi ciency and eff ectiveness of a transit agency regardless of whether the service is contracted out or kept in house. Privatization appeals to citizen and politician desires for more cost-eff ective methods of service delivery. For this reason, it is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 15 publications
2
38
0
1
Order By: Relevance
“…After applying these parameters, our population consisted of 236 transit agencies, which can generally be characterized as agencies that operate small and medium-sized bus transit systems in urbanized areas where they are the lone providers of public transit services. Th is defi nition of our population of interest is consistent with long-standing practice in research regarding performance in the transit industry (Boschken 1992; Leland and Smirnova 2009;Perry and Babitsky 1986;Zullo 2008).…”
Section: Sample Selection and Survey Methodologymentioning
confidence: 97%
“…After applying these parameters, our population consisted of 236 transit agencies, which can generally be characterized as agencies that operate small and medium-sized bus transit systems in urbanized areas where they are the lone providers of public transit services. Th is defi nition of our population of interest is consistent with long-standing practice in research regarding performance in the transit industry (Boschken 1992; Leland and Smirnova 2009;Perry and Babitsky 1986;Zullo 2008).…”
Section: Sample Selection and Survey Methodologymentioning
confidence: 97%
“…While almost none of the research published before 2000 took competition into account in their empirical analyses (De Borger, Kerstens, & Costa, ), more recent studies have controlled for competition for the contract. Leland and Smirnova () compared the evolution in efficiency and effectiveness of U.S. urban bus services, and found that privately owned and managed transit systems were no longer more efficient and effective providers than government‐owned agencies. They pointed to the lack of competition between contractors and higher transaction costs as factors.…”
Section: Empirical Evidence On Public and Private Delivery Costs And mentioning
confidence: 99%
“…collectively, these studies have identified a wide range of transit system characteristics and service operation variables along with service area characteristics and structural variables that influence the performance of local public transit systems. Key variables that have been found to influence aspects of transit system performance include ser-vice area population density (Fielding et al, 1978;leland & Smirnova, 2008), institutional structure, that is, whether special-purpose authority vs. unit of general purpose local government (leland & Smirnova, 2008;Perry & babitsky, 1986), size and scale of operations (brown & thompson, 2008;leland & Smirnova, 2009;Perry & babitsky, 1986), and privatization of service delivery (giuliano, 1981;leland & Smirnova, 2008;Mccullough, taylor, & wachs, 1998;Perry & babitsky, 1986).…”
Section: Methodsmentioning
confidence: 99%